Regional Economic Activity and Stock Returns - Smajlbegovic, Esad (Journal of Financial and Quantitative Analysis, 2019)
This paper studies the diffusion of regional macroeconomic information into stock prices. I identify all U.S. states that are economically relevant for a company through textual analysis of annual reports and find that economic activity forecasts of company-relevant regions positively predict cross-sectional stock returns. Information arising from all relevant states is more important than that relating to the headquarter state alone. These forecasts also predict firms’ performance and earnings surprises, suggesting that the return predictability stems from future cash flows that are gradually reflected in prices. Finally, regional information takes longer to be incorporated into prices among difficult-to-arbitrage stocks.